2014
DOI: 10.1155/2014/710781
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Natriuretic Peptide and Renal Dopaminergic System: A Positive Friendly Relationship?

Abstract: Sodium metabolism by the kidney is accomplished by an intricate interaction between signals from extrarenal and intrarenal sources and between antinatriuretic and natriuretic factors. Renal dopamine plays a central role in this interactive network. The natriuretic hormones, such as the atrial natriuretic peptide, mediate some of their effects by affecting the renal dopaminergic system. Renal dopaminergic tonus can be modulated at different steps of dopamine metabolism (synthesis, uptake, release, catabolism, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 87 publications
(138 reference statements)
0
11
0
Order By: Relevance
“…ANP was discovered in 1981 by de Bold et al, (1981) as a 28-amino acid peptide that is synthesized and stored in atrial and ventricular myocytes and released in response to various stimuli, such as stretching of the cardiac wall, endothelin, diverse cytokines, or adrenergic agents ( Rukavina Mikusic et al, 2018b ). Subsequently, it has been described that the kidney has all the biosynthetic machinery to produce ANP, its receptors, and the catabolic enzymes to degrade it ( Wu et al, 2009 ; Choi et al, 2014 ). Given its actions in the kidney, it has been proposed that ANP could be involved in the pathogenesis of chronic kidney disease (CKD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ANP was discovered in 1981 by de Bold et al, (1981) as a 28-amino acid peptide that is synthesized and stored in atrial and ventricular myocytes and released in response to various stimuli, such as stretching of the cardiac wall, endothelin, diverse cytokines, or adrenergic agents ( Rukavina Mikusic et al, 2018b ). Subsequently, it has been described that the kidney has all the biosynthetic machinery to produce ANP, its receptors, and the catabolic enzymes to degrade it ( Wu et al, 2009 ; Choi et al, 2014 ). Given its actions in the kidney, it has been proposed that ANP could be involved in the pathogenesis of chronic kidney disease (CKD).…”
Section: Introductionmentioning
confidence: 99%
“…(2) At tubular level: ANP inhibits sodium reabsorption throughout the nephron ( Choi et al, 2014 ). In the proximal tubule, ANP inhibits different Na + transporters, as the Na + /H + exchanger, Na/Pi type IIa cotransporter, and the Na + , K + -ATPase, and also counteracts angiotensin-stimulated sodium reabsorption ( Theilig and Wu, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…(11,12,22) Moreover, it has been shown that ANP increases the synthesis of renal dopamine by stimulating the activity of dopa decarboxylase. (31) In this insulin-resistance model, and as a result of low levels of plasma ANP, a reduction in both synthesis and uptake of dopamine by tubular cells would be expected as a consequence of reduced…”
Section: Discussionmentioning
confidence: 94%
“…Peripheral dopamine plasma values are rarely reported in scientific literature, despite the fact that the dopaminergic system plays an important role in the cardiovascular system [ 44 ]. Dopamine might play a role in hypertension [ 55 ] and the role of a dopaminergic renal system in hypertension is discussed [ 56 ]. A recent study showed an inverse correlation between plasma dopamine and C-peptide concentrations in patients with diabetes, emphasizing modulating effects [ 57 ].…”
Section: Discussionmentioning
confidence: 99%